Behavior of plasmid-mediated Colistin resistance gene in urban Water environment - Vu, Thi My Hanh (2020)
Behavior of plasmid-mediated Colistin resistance gene in urban Water environment. The comparable levels of mcr-1 in urban sewage in Vietnam and Japan showed the prevalence of the transmissible colistin resistance gene. Domestic wastewater is thus considered an important monitoring target for mcr-1 in urban cities. The presence of mcr-1 is significantly correlated with 16S rRNA genes, blaNDM-1 and crAssphage,suggesting the co-occurrence of these genes in polluted water samples. Whereas wastewater treatment could reduce mcr-1 copy numbers, final effluents after chlorination still contained mcr-1. In addition to conventional indices of total coliform and E. coli, it is necessary to control mcr-1 released into aquatic environments from wastewater treatment plants.